Sosialisasi Pencegahan Pungutan Liar - Surjanti; Erly Pangestuti (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
In carrying out the main tasks and functions of the Sub Unit of Prevention of the UPP Saber Extortion, are preventing illegal levies and eradicating illegal levies by providing socialization, distributing pamphlets, placing banners in places where illegal levies are suspected, including in service offices. public. In carrying out its activities, the eradication unit must be able to realize accountability and integrity of the apparatus in carrying out its main duties and functions. In this case, there are still many obstacles in its implementation, including an orderly working mechanism and no standard operating procedure. In addition, extortion seems to have been a habit of the community for a long time so it is difficult to get rid of it.